ANALISIS DATA MAKRO EKONOMI DAERAH SEBAGAI INDIKATOR CAPAIAN KINERJA SERTA LANDASAN PROYEKSI MAKRO EKONOMI KABUPATEN MADIUN PADA TAHUN 2022-2027 - Rila Anggraeni (Pemerintah Kabupaten Madiun, 2022)
The activity of preparing the Madiun Regency Strategic Plan for Development is a means for assessing past economic performance achievements and predicting regional economic conditions and performance in the next 5 years. To predict future macroeconomic data for Madiun Regency, it is necessary to present statistical data projections based on regional macroeconomic indicators such as economic growth, inflation, regional income levels, poverty, unemployment, and regional economic structure, namely GRDP (Gross Regional Domestic Product), which is used as material for regional development planning, especially in the economic field. The main objective of economic development is to create high economic growth and eliminate or reduce poverty, income inequality, and unemployment. Based on the projected data presented using regional macroeconomic indicators, it can be concluded that each sector experiences growth in line with improving health and economic conditions. It is predicted that economic growth will improve with an estimated achievement in 2021 of 1.56 and an increase of 1.92 in 2022 to 3.04 in 2027. While the projected GRDP Per Capita in 2021 is 28.03 million per capita and 28.47 million in 2021. in 2022 then increase to 32.7 million in 2027. Based on the results of the GRDP projection per sector, it is known that each sector experiences growth in line with improving health and economic conditions. Several sectors such as health and information communication continue to grow rapidly in line with the community's need for better health services and sophisticated information and communication networks.